(3GdhGajs - (3GdcGTj Ch GdcGTGfj, GdajV, GdeJCdg GdMcje, eMSf Hf eQJVi Hf ajV Gddg eMehO, J (B1090 (3gs
(3ChdgG (B:s
(3GdMeO ddg (B... (3cJGH GdWgGQI hGdJRjf (B.. (3GdBjGJ bGd Gddg Ld hYR (B{ (3hKjGHc aWgQ (B} (3hbGd JYGdi (B{ (3Ef Gddg jMH GdJhGHjf hjMH GdeJWgQjf (B} (3hbGd SHMGfg (B{ (3ajg QLGd jMHhf Cf jJWgQhG hGddg jMH GdeJWgQjf (B} ...s
(3BNQgG (B:s
... (3hGLYdg aj QCSj , bGd c dG HCS , HjGf aj GdJgPjH Med GdNeQ gGgfG Ydi WHjN GdJeQ GdPGgH KdKGg ceG aj GdLfj GdSGHb BNQ CHhGH bVA GdJaK hGdJRjf hHJeGegG Je cJGH GdWgGQI hGdJRjfs
(3JHUQI GdYfhGf (B:s
(3aj Ydhe GdOjfs
(3JHUQI GdeDda (B:s
(3jbhd GdRQcdj(B: (3hQO GSeg (B" (3eMSf Hf eQJVi (B" (3h (B" (3eMSf Hf eMqeO (B" (3h (B" (3eMeO eMSf (B" (3hbjd dg (B" (3GdajV (B" (3hYQa LOg HajV (B... (3Gddg hHGdajV(B. (3hLGAJ fSHJg (B" (3GdcGTj (B" (3h (B" (3GdcGTGfj (B" (3h (B" (3GdbGTGfj (B" (3hjbGd dg(B: (3edG eMSf ajV GdcGTjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 290s
Keywords: (3GdMOjK hGdeUWdMs